Men's accounts of anxiety: A photovoice study - Sarah K. McKenzie; Mary T. Kelly; Emily Cooney; John L. Oliffe (SSM: Qualitative Research in Health, 2023)
Anxiety disorders are one of the most commonly diagnosed mental illnesses amongst men. Despite this, research exploring men's lived experiences of anxiety is sparse. The current photovoice study offers key insights to the understandings of nineteen New Zealand based men aged 24-62 who live with anxiety disorders. Using reflexive thematic analysis to analyse individual in-depth photo-elicitation interviews, two overarching themes were inductively derived: 1) Experiencing and embodying anxiety wherein men's internalized anxiety was characterised as an amorphous and unpredictable entity which could render them powerless, isolated and trapped; 2) Managing uncertainties in which men employed several strategies to control their anxiety amid an array of challenging circumstances. Discussed within a masculinities framework, the findings reveal complex lived experiences embedded in men's social worlds and gendered practices. Findings indicate the need to develop targeted interventions for men experiencing anxiety.